2021
DOI: 10.1039/d1na00050k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of aerospace epoxy composites reinforced with 2D nano-fillers: current status and road to industrialization

Abstract: Epoxy composites find application in the aerospace industry. Although epoxy is a high-performance polymer, its fracture toughness is compromised due to its highly cross-linked nature. Nanomaterials such as carbon nanotubes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 220 publications
1
52
0
Order By: Relevance
“…Epoxy resins are extensively used in a wide range of applications [1], including adhesives [2,3], coatings [4,5], and high-performance composites [6,7], among others. However, as one of the main drawbacks is their inherent brittleness, much research has gone into finding ways to increase their toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins are extensively used in a wide range of applications [1], including adhesives [2,3], coatings [4,5], and high-performance composites [6,7], among others. However, as one of the main drawbacks is their inherent brittleness, much research has gone into finding ways to increase their toughness.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that MB013 is the most elastic sample, but it also presents the lowest mechanical resistance. This could be explained by an improved load transfer due to the presence of amino-functionalized graphene [48,49]. The addition of a supplementary amount of iron oxide to this formulation led to higher mechanical resistance (MB014) probably due to a reinforcing effect of the filler.…”
Section: Scheme 1 Graphical Representation Of the Graphene Stacks' Th...mentioning
confidence: 98%
“…The use of 2D materials, especially graphene, for epoxy resin reinforcement has been extensively documented. Important improvements in modulus, mechanical strength, toughness, and hardness have been reported, and the reader may consult interesting reviews [ 5 , 16 , 31 , 32 ]. In general, 2D nanomaterials have been studied in depth; however, the study of MXene-modified ERs is still in its beginning.…”
Section: Properties and Applications Of Mxene/epoxy Compositesmentioning
confidence: 99%
“…Two-dimensional nanomaterials are now very popular because of their outstanding properties derived from their high aspect ratio and specific surface area, surface chemistry, and quantum-size effects. Two-dimensional nanomaterials are excellent reinforcement phases for toughening and strengthening epoxy resins [ 5 ]. Graphene, a two-dimensional layer of carbon atoms sp 2 , is probably the most widely used 2D material.…”
Section: Introduction Epoxy Resins and Mxenesmentioning
confidence: 99%
See 1 more Smart Citation